Structural, morphological, and optical properties of nanocrystalline zirconia synthesized via modified thermal treatment technique - Keiteb, Aysar Sabah; Saion, Elias; Zakaria, Azmi; Ahmad, Ahmad Fahad; Yakubu, Abubakar (2015)
This article reports the synthesis of Zirconium oxide nanoparticles by modified thermal treatment technique. The metal precursor; Zirconium (IV) acetate hydroxide, and the capping agent, PVP were dissolved in deionized water. The homogeneous mixture underwent calcination in furnace with different temperatures of 600, and 900 °C to obtain pure zirconia nanoparticles in crystalline phase and remove organic compounds. The structural studies of ZrO2 nano- particles have been carried out using XRD, SEM and TEM. The XRD spectra showed that the formation of crystalline structure of the metal oxide nanoparticles has been achieved after calcination process. The optical properties were investigated using a UV–Vis spectrophotometer, which showed a decrease in the band gap with increasing calcination temperature. These results prove that, the modified thermal treatment method is a simple technique that can produce quite pure metal oxide nanoparticles with no additional chemicals needed.